Heritage-Cities and Tourism. Toward a New Species of Public Space (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2017)
The Shared Vision contained in the New Urban Agenda (2016) indicates a necessary participatory commitment toward the â€œright to the cityâ€, the right to adequate housing, gender equality, accessible urban mobility for all, disaster management and resilience and sustainable consumption. To pursue sustainable development, the Agenda stimulates action through a collective vision of political commitment that considers diverse realties and emerging contexts, social inclusion, land tenure, the value of public space and the sustainable leverage of natural and cultural heritage, viewed as priority and strategic components for future urban development. Through the observation and critical analysis of phenomena raised by a case study, this text examines a topical and highly controversial issue involving the public spaces and constructions of a heritage-city. In particular, the city of Matera where, since 1993 â€“ the Sassi â€“ are under the protection of UNESCO, the same city that in 2015 was named European Capital of Culture 2019. With respect to sustainable development, in this particular case attention must be focused on the unavoidable and rapid transition occurring in architectural-urban space under the pressures exerted by mass tourism, typical of sites in the attractive Mediterranean contexts of the World Heritage List.